2015
DOI: 10.1182/blood-2014-09-601302
|View full text |Cite
|
Sign up to set email alerts
|

Boost and loss of immune responses against tumor-associated antigens in the course of pregnancy as a model for allogeneic immunotherapy

Abstract: Key Points Pregnancy recalls short-lived immunity against TAAs mimicking antileukemic responses after allogeneic stem cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
1
11
0
1
Order By: Relevance
“…Overall, we were able to detect LAA peptide‐specific T cells in HIs with a prevalence of 34%, whereas 15 out of 100 HIs responded to more than one antigen. In previous studies, the prevalence of LAA‐specific T cells was assessed by quantifying IFN‐γ specific messenger‐RNA after stimulating HLA‐A*02:01‐positive CTLs with LAA peptide‐pulsed T2 cells . In this context, LAA‐specific T‐cell responses have been reported in up to 32% of HIs, corresponding to our data .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Overall, we were able to detect LAA peptide‐specific T cells in HIs with a prevalence of 34%, whereas 15 out of 100 HIs responded to more than one antigen. In previous studies, the prevalence of LAA‐specific T cells was assessed by quantifying IFN‐γ specific messenger‐RNA after stimulating HLA‐A*02:01‐positive CTLs with LAA peptide‐pulsed T2 cells . In this context, LAA‐specific T‐cell responses have been reported in up to 32% of HIs, corresponding to our data .…”
Section: Discussionsupporting
confidence: 77%
“…In previous studies, the prevalence of LAA-specific T cells was assessed by quantifying IFN-γ specific messenger-RNA after stimulating HLA-A*02:01positive CTLs with LAA peptide-pulsed T2 cells [12,23]. In this context, LAA-specific T-cell responses have been reported in up to 32% of HIs, corresponding to our data [12,23]. Since naïve T cells have been characterized to display only minor cytokine expression [37], all detected responses in this study supposedly originate from the effector/effector memory T-cell pool.…”
Section: Discussionmentioning
confidence: 99%
“…Lutz et al . demonstrated recently that elevated expression of WT1 in the uterine tissue during pregnancy can induce higher frequencies of WT1‐specific CTLs vanishing some months after the delivery . Taking advantage of this population of WT1‐specific CTLs in healthy subjects, we propose that the adoptive transfer of WT1‐specific CTLs after treatment directly from donor to patient might control any residual blast, a considerable potential demonstrated for virus‐specific CTLs …”
Section: Discussionmentioning
confidence: 92%
“…40 This cross-reactivity may explain the presence of WT1-specific T cells in healthy donors found by Wang et al 34 and Weber et al 41 Lutz et al demonstrated recently that elevated expression of WT1 in the uterine tissue during pregnancy can induce higher frequencies of WT1-specific CTLs vanishing some months after the delivery. 42 Taking advantage of this population of WT1-specific CTLs in healthy Figure 4. WT1-specific T cells in an AML patient in CR.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the decline of CTAg‐specific immunity is likely to reflect the absence of available CTAg antigen following orchidectomy and as such is similar to the kinetics of decline of adaptive immunity following the clearance of acute viral and bacterial antigens . In support of this, a recent publication showed that placental‐specific T‐cell immune responses can be established during pregnancy but that these are short‐lived and became undetectable in the periphery after delivery . It also remains possible that CTAg‐specific immunity does in fact persist but becomes unresponsive to antigenic stimulation due to increased expression of inhibitory checkpoint receptors such as PD‐1 on the cell surface, or an increase in regulatory cells such as T‐regulatory cells (Tregs) or myeloid‐derived suppressor cells (MDSCs) in the blood following treatment, as has been described previously for HPV‐specific responses in oropharyngeal patients .…”
Section: Discussionmentioning
confidence: 94%